Bas relief of a peacock - Temples of India Project Team (Jio Institute, 2024)
Debris from the original temple was salvaged when the current temple was reconstructed in the 1940s. These have been assembled in parts to form the jagati (raised platform). However, it is not known where they were located in the original temple. Bas relief of a peacock picking the food from the ground. A ring is placed on the neck of the bird.